Electrochromic device (ECD) cell characterization on electron beam evaporated MoO3 films by intercalating/deintercalating the H+ ions - Sivakumar, R.; Gopinath, Chinnakonda S.; Jayachandran, M.; Sanjeeviraja, C. (Current Applied Physics, 2007)
Thin films of molybdenum oxide (MoO3) is one of the most interesting layered intercalation materials because of its excellent application in solid state batteries, large-area window and display systems. In recent years there has been considerable interest in variable transmittance electrochromic devices (ECD) based on Li+, H+ and K+ intercalation in transition metal oxide (MoO3) thin films. In the present investigation, thin films of MoO3 were prepared by electron beam evaporation technique on microscopic glass and fluorine doped tin oxide (FTO) coated glass substrates for the application in electrochromic device cells. The compositional stoichiometry of the films was studied by X-ray photoelectron spectroscopy (XPS). The electrochromic nature of the films has been analyzed by inserting H+ ions from the H2SO4 electrolyte solution using the cyclic-voltammetry (CV) technique. We studied the electrochromic device cells (ECD) incorporating an evaporated MoO3 thin films as electrochromic layers. The devices exhibit good optical properties with low transmittance values in the colored state, which make them suitable for large-area window applications. The maximum coloration efficiency of the cell was observed at about 70 cm(2)/c. (c) 2005 Published by Elsevier B.V.
Keywords: coloration efficiency; electrochromic device cells; molybdenum oxide thin films; optical density; stoichiometry